Hyperfractionated radiotherapy with concurrent weekly paclitaxel and carboplatin for locally advanced unresectable head and neck squamous cell carcinoma - Perumal S; Kumari PM; Rajendran K (Journal of Medical and Scientific Research)
Background: Squamous cell carcinoma of the head and neck (HNSCC) is a major contributor to cancer-related morbidity and mortality worldwide, with particularly high incidence rates in India and Tamil Nadu. Locally advanced, unresectable HNSCC presents a significant therapeutic challenge. This study aimed to assess the immediate loco-regional response rates following treatment with hyperfractionated radiotherapy combined with concurrent weekly paclitaxel and carboplatin, as well as to evaluate acute toxicity and prognostic factors influencing treatment outcomes.